Molecular identification of two Eimeria species, E. uekii and E. raichoi as type B, in wild Japanese rock ptarmigans, Lagopus muta japonica - Makoto Matsubayashi; Sayaka Tsuchida; Atsushi Kobayashi; Tomoyuki Shibahara; Hiroshi Nakamura; Koichi Murata; Kazunari Ushida (International Journal for Parasitology: Parasites and Wildlife, 2018)
Thus far, two types of Eimeria parasites (E. uekii and type B) have been morphologically identified in wild Japanese rock ptarmigans, Lagopus muta japonica. Although high prevalences were reported for these parasites, genetic analyses have not been conducted. We first clarified the phylogenetic positions of two eimerian isolates using genetic analyses of 18S rRNA and mitochondrial cytochrome c oxidase subunit I gene regions. Consequently, of 61 samples examined, 21 and 11 samples were positive for E. uekii and type B, respectively. Additionally, the infection rate increased in the summer. Molecular analyses revealed both Eimeria isolates formed their own clusters; E. uekii was included in clades of chicken Eimeria and type B was include in clades of turkey Eimeria. Based on our findings in this study and previous data, we herein propose type B as E. raichoi. These genetic data will be helpful to conduct detailed classification and understand the impact of these parasites for conservation of endangered Japanese rock ptarmigans. Keywords: Japanese rock ptarmigan, Eimeria raichoi, Eimeria uekii, Lagopus muta japonica